PENGARUH NON PERFORMING LOAN TERHADAP RETURN ON ASSET (Survey pada PT Bank Negara Indonesia (Persero) Tbk) - Agi Rosyadi; Yuyun Yuniasih (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2020)
ABSTRACTThe purpose of this study was to determine and analyze Non-Performing Loans and Returns on Assets and the magnitude of the influence of Non-Performing Loans on Return On Assets at PT Bank Negara Indonesia (Persero) Tbk period 2007-2017. The research approach uses a quantitative approach with explanatory methods. The sampling technique uses purposive sampling with time series analysis using secondary data, namely the financial statements of PT Bank Negara Indonesia (Persero) Tbk for the period 2007-2017. The statistical analysis technique used is simple linear regression through the classical assumption test. The results showed the relationship between variables having closeness with a very low level of relationship. Based on the analysis, the condition of Non-Performing Loans and Returns on Assets in PT Bank Negara Indonesia (Persero) Tbk 2007-2017 period tends to fluctuate. The amount of contribution of the influence of Non Performing Loans on Return On Assets at PT BNI (Persero) Tbk amounted to 37.30%. From the results of hypothesis testing it can be concluded that there is no significant influence of Non Performing Loans on Return On Assets at PT BNI (Persero) Tbk for the period 2007-2017.Keywords: non performing loan; retun on asset.ABSTRAKTujuan penelitian ini adalah untuk mengetahui dan menganalisis Non Performing Loan dan Retun on Asset serta besarnya pengaruh Non Performing Loan terhadap Return On Asset pada PT Bank Negara Indonesia (Persero) Tbk periode 2007-2017. Pendekatan penelitian menggunakan pendekatan kuantitatif dengan metode eksplanatory. Teknik pengambilan sampel menggunakan purposive sampling dengan analisis time series menggunakan data sekunder yaitu laporan keuangan PT Bank Negara Indonesia (Persero) Tbk periode 2007-2017. Teknik analisis statistik yang digunakan adalah regresi linier sederhana dengan melalui uji asumsi klasik. Hasil penelitian menunjukkan hubungan antara variabel memeliki keeratan dengan tingkat hubungan yang sangat rendah. Berdasarkan hasil analisis, kondisiNon Performing Loan dan Retun on Asset pada PT Bank Negara Indonesia (Persero) Tbk Periode 2007-2017 cenderung mengalami fluktuatif. Besarnya kontribusi pengaruh Non Performing Loan terhadap Return On Asset pada PT BNI (Persero) Tbk sebesar 37.30%. Dari hasil pengujian hipotesis dapat disimpulkan bahwa tidak terdapat pengaruh signifikan Non Performing Loan terhadap Return On Asset pada PT BNI (Persero) Tbk periode 2007-2017. Kata Kunci: non performing loan; retun on asset.